2020
DOI: 10.1097/der.0000000000000666
|View full text |Cite
|
Sign up to set email alerts
|

Nickel: Intrinsic Skin Sensitization Potency and Relation to Prevalence of Contact Allergy

Abstract: Nickel remains the most commonly identified contact allergen. However, it has proven difficult to demonstrate significant skin-sensitizing activity for nickel in toxicology tests, which typically have indicated a weak skin sensitization potential. Information indicates that in vivo assays are not predictive of dermal sensitization hazard or potency for nickel due to a human-specific mechanistic route for nickel sensitization that animals lack. A similar rationale will apply to in vitro alternatives—although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Nickel is a moderate allergen that sparks its sensitization potency by inflammation, which is obligatory during the tattooing procedure and also during piercing of ears, the major source of nickel allergy in women. 12,106,107 Eighty percent of tattooed undergraduate students in Italy were pierced. 108 About one third of the tattooed had body piercings in an American study.…”
Section: Confounding Variables For the Interpretation Of Pt Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel is a moderate allergen that sparks its sensitization potency by inflammation, which is obligatory during the tattooing procedure and also during piercing of ears, the major source of nickel allergy in women. 12,106,107 Eighty percent of tattooed undergraduate students in Italy were pierced. 108 About one third of the tattooed had body piercings in an American study.…”
Section: Confounding Variables For the Interpretation Of Pt Resultsmentioning
confidence: 99%
“…During clinical relevance assessment of positive PT reactions or in epidemiological studies, confounding exposures should be considered. Nickel is a moderate allergen that sparks its sensitization potency by inflammation, which is obligatory during the tattooing procedure and also during piercing of ears, the major source of nickel allergy in women 12,106,107 . Eighty percent of tattooed undergraduate students in Italy were pierced 108 .…”
Section: Introductionmentioning
confidence: 99%
“…One underlying mechanism may be the lack of the primate-restricted histidine duplet (H456/H458) in murine and other rodent TLR4 [117]. Ethically questionable human experiments from the 1960s showed that exposure to NiCl 2 sensitized 48% of individuals [194,195]. In real life, Ni allergy has been associated with very low exposure concentrations and skin injury (piercings) [74,196].…”
Section: Predictive Tests For Sensitizing Propertiesmentioning
confidence: 99%
“…Considerations of potency are relevant when exploring the ability of nickel derived from implants to cause sensitization because, although the prevalence of nickel allergy is relatively high among the general population, nickel is actually regarded as having limited, and at best, intermediate, sensitizing potency in humans. 42 In this context, nickel is known to be significantly less potent than many chemicals commonly associated with ACD. 42 In summary, the ability of a contact allergen, in this case nickel, to induce sensitization will be influenced by the intrinsic potency of the allergen, the extent of exposure (and, in particular, local concentrations of the allergen), the availability of DCs, the stimulation of danger signals, and anatomical alignment with draining lymph nodes.…”
Section: Exposure To Nickel In Metal Implants and The Acquisition Of ...mentioning
confidence: 99%
“… 42 In this context, nickel is known to be significantly less potent than many chemicals commonly associated with ACD. 42 In summary, the ability of a contact allergen, in this case nickel, to induce sensitization will be influenced by the intrinsic potency of the allergen, the extent of exposure (and, in particular, local concentrations of the allergen), the availability of DCs, the stimulation of danger signals, and anatomical alignment with draining lymph nodes. Although it is acknowledged that under most conditions of exposure (other than skin exposure), it will not be possible to evaluate many (if any) of these variables, it is important to appreciate that exposure per se, especially exposure measured at a systemic level, will not necessarily equate with the risk of sensitization.…”
Section: Exposure To Nickel In Metal Implants and The Acquisition Of ...mentioning
confidence: 99%